UKRAINIAN ETHNOPEDAGOGY AS A FACTOR OF ENRICHMENT EDUCATIONAL IMPACT ON THE INDIVIDUAL - Furduy, S.B. (Pedagogy of Higher and Secondary Education, 2022)
The article deals with the question of Ukrainian ethnopedagogics as a factor o f educational influence over personality.